2011
DOI: 10.1039/c1nr10883b
|View full text |Cite
|
Sign up to set email alerts
|

Development of a mass-producible on-chip plasmonic nanohole array biosensor

Abstract: We have developed a polymer film based plasmonic device whose optical properties are tuned for measuring biological samples. The device has a circular nanohole array structure fabricated with a nanoimprint technique using a UV curable polymer, and then gold thin film is deposited by electron beam deposition. Therefore, the device is mass-producible, which is also very important for bioaffinity sensors. First the gold film thickness and hole depth were optimized to obtain the maximum dip shift for the reflectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 48 publications
(48 reference statements)
1
60
1
Order By: Relevance
“…The FWHM value increases monotonically with the increasing nanowell depth, while FH shows a descending trend. [ 34 ] It is worth noting that the narrowest linewidth of 9.4 nm is achieved in this study from a 40 nm nanowell depth. This value is approximately 1.6 times larger than the one obtained in the previous section and also much higher than many other high-performance plasmonic sensors, such as the bimetallic Au on Ag nanohole arrays (about 9 × 10 −3 nm −1 ) [ 33 ] and the Au bottom-fi lled nanohole arrays (19.6 × 10 −3 nm −1 ).…”
Section: Optimization Of Nanowell Depthmentioning
confidence: 60%
“…The FWHM value increases monotonically with the increasing nanowell depth, while FH shows a descending trend. [ 34 ] It is worth noting that the narrowest linewidth of 9.4 nm is achieved in this study from a 40 nm nanowell depth. This value is approximately 1.6 times larger than the one obtained in the previous section and also much higher than many other high-performance plasmonic sensors, such as the bimetallic Au on Ag nanohole arrays (about 9 × 10 −3 nm −1 ) [ 33 ] and the Au bottom-fi lled nanohole arrays (19.6 × 10 −3 nm −1 ).…”
Section: Optimization Of Nanowell Depthmentioning
confidence: 60%
“…Nakamoto et al showed that the metal thickness does not signicantly change the resonance wavelength of the metal-solution plasmon band. 21 In contrast to this enhanced transmission, optically thin lms show signicantly suppressed transmission. [22][23][24] Surface roughness will have a strong effect on the bandwidth of the plasmon band, 25 but does not change the resonance wavelength.…”
Section: Introductionmentioning
confidence: 95%
“…Recent work has now introduced reflection-mode measurements also for nanoplasmonic sensors. 90,91 Using template-stripping methods, backside reflection-mode nanoplasmonic sensor has also been demonstrated, 92 wherein the optical paths and fluidic paths are decoupled as with conventional SPR.…”
Section: Plasmon Spectroscopy For High-resolution Biosensingmentioning
confidence: 99%